2020
DOI: 10.3390/electronics9050876
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Technologies in Personal Learning Environments of Intercultural Contexts: Individual and Group Tasks

Abstract: This paper presents the results of the analysis of the personal learning environments (PLE) used individually and in groups by fifth grade primary education students. The main objective was to determine if the use of mobile technologies in the students’ PLEs encouraged their school integration and learning in intercultural communities. For this, a content analysis of the students’ responses to an ad hoc interview was carried out, with a content validity index of 0.89. The students represented their answers usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 134 publications
(167 reference statements)
1
6
0
2
Order By: Relevance
“…The complexity of cyberbullying caused by religious or cultural intolerance, together with the constant increase in intercultural classrooms [25], show the importance of this research. This attempts to respond to the knowledge gaps detected in the few studies on this type of cyberbullying [26].…”
Section: Literature Reviewmentioning
confidence: 95%
“…The complexity of cyberbullying caused by religious or cultural intolerance, together with the constant increase in intercultural classrooms [25], show the importance of this research. This attempts to respond to the knowledge gaps detected in the few studies on this type of cyberbullying [26].…”
Section: Literature Reviewmentioning
confidence: 95%
“…There has been a significant amount of research studies about PLE within different contexts with theoretical and empirical foci that include its definition, origin, evolution, pedagogical and technological implications, supportive tools, instruction designs, and more (Castañeda, Tur, & Torres-Kompen, 2019;Gallego-Arrufat & Chaves-Barboza, 2014;R., Edirisingha, Canaleta, Alsinaa, & Monguet, 2019;Tomé-Fernández, Curiel-Marín, & Caraballo, 2020). These studies have identified multiple benefits of the use of learning technologies especially within PLE as it is student-centered and because of its pedagogical strategies that support their functioning (Bustos et al, 2012;García & González, 2017;Scherer & Ferrari, 2018;V.…”
Section: Technology For Personalized Learningmentioning
confidence: 99%
“…In primary school, there are experiences based on the use of mobile technologies in the students' PLEs. These experiences are focused on promoting integration in school and intercultural competencies [26][27][28].…”
Section: Introductionmentioning
confidence: 99%